Rethinking Directions of Politics and Bureaucracy Post Neo-Liberalism: An Indonesian Experience - Deddy Bratakusumah (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2019)
The reforms triggered by the economic crisis that hit Indonesia and a number of other Asian countries in 1998 have resulted in not only an improvement over a system that has been in force for the past 30 years but also fundamental changes. Although reform is born by a spirit of renewal, in response to the failure of the state to develop a system that can generate prosperity and justice for the people, both in the political and economic fields, but in the process has not produced a better relationship system between politics and public administration, which is professional, effective, efficient and free from corruption. This unsuccessfulness is predictable because the administrative reform is not based on a strict economic school. We had previously applied the Keynesian school, then Neo-liberalism, up until now the world is still searching for a new school. No exception for Indonesia. Reform has established a new system, completely different from the previous system, but without consistent ideology and paradigm. The lack of clear direction is the cause of the failure of administrative reform in Indonesia. The paper will analyze the cause of this unsuccessful, and propose recommendations for improvement.